Hypomagnesemia in Iraqi Diabetic Patients and Healthy Controls: An Exploratory study - Abdulaziz, Lewai S. (AL-Kindy College Medical Journal, 2010)
Background: Diabetes mellitus has been suggestedto be the most common metabolic disorderassociated with magnesium deficiency, and becauseavailable data suggest that adverse outcomes areassociated with hypomagnesemia, it is prudent thatroutine surveillance for hypomagnesemia be doneand the condition be treated whenever possible.Aim of the study:To explore the serum Mgconcentrations of diabetic patients and healthycontrols in our locality.Mehtods: One hundred and forty four diabeticpatients (22 with type I and 122 with type II diabetesmellitus) recruited from the outpatient diabetes clinicat the Specialized Center For Endocrine DiseasesBaghdad (62 patients), National Diabetes Center-AlMustansiria University (20 patients), and fromprivate endocrinologic practice clinics in Baghdad(62 patients), during the period from 1st October2005 to 30th April 2006. Ninety non-diabetic healthycontrols matched for age and sex were participated inthis study. Exclusion criteria for both groupsincluded diarrhea and loop diuretics. None weretaking Mg supplements. Level of Mg and Albuminwere determined spectrophotometerically in thesame serum samples.Results: Mean serum Mg concentrations of thediabetics was significantly lower than in controls (p